Web-Based Employee Payroll Information System at Bank Perkreditan Rakyat Ingertad Bangun Utama Ltd - Suhesti Handayani; Annafi' Franz; Budi Rachmadani (TEPIAN, 2023)
This research is motivated by salaries that have not been maximized at the company Bank Perkreditan Rakyat Ingertad Bangun Utama Ltd because it still keeps documents in hard file form. With this web-based employee payroll information system, it is easier for admins to access salary data by accessing the web. The tool used to describe the system model is an Entity Relationship Diagram (ERD). To implement this payroll information system, supporting components are needed in order to work properly. These components use Laravel programming framework and store database in MySQL and use Talwind CSS design to make design easier. The results of research and applications can overcome the problems that exist in companies that do not yet have a payroll application and can be used to process salaries in the company.